MOTHERS’ EXPERIENCES OF RESPONSIVE FEEDING AMONG STUNTED CHILDREN AGED 6–23 MONTHS : A QUALITATIVE STUDY - Heina Azzahra Putri; Woro Setia Ningtyas; Widati Fatmaningrum (UNIVERSITAS AIRLANGGA, 2026)
Background: Stunting remains a major public health problem, with a global prevalence of 23.2% and 21.5% in Indonesia in 2024, where it is targeted to be reduced to 14%. Chronic undernutrition, especially from birth to 2 years, significantly contributes to impaired linear growth. Optimal feeding practices, including responsive feeding, are critical in ensuring adequate nutrient intake and preventing growth faltering. This study aims to explore how mothers implement responsive feeding practices among stunted children aged 6–23 months. Method: This study uses a qualitative method with a phenomenological approach. Informants were mothers of stunted children aged 6–23 months in Pesantren Subdistrict, Kediri East Java, selected using purposive sampling based on specific criteria. Data were collected through semi-structured interviews and analyzed thematically. Result: Four theme emerged: recognition of hunger and satiety cues, mother–child interaction during feeding, introduction of new foods and responses to refusal, and challenges in complementary feeding. Although most mothers recognized hunger and satiety cues, feeding practices were often distracted, and food refusal commonly led to lack of reintroduction and substitution with snacks or milk. Conclusion: Responsive feeding practices were not consistently implemented according to optimal nutrition principles. Feeding behaviors tended to be situational rather than structured, potentially affecting children’s daily energy intake. Strengthening caregiver education on responsive feeding is essential to improve feeding practices and support optimal child growth.